1999
DOI: 10.1017/s0007485399000747
|View full text |Cite
|
Sign up to set email alerts
|

The host range, annual cycle and parasitoids of the African rice gall midge Orseolia oryzivora (Diptera: Cecidomyiidae) in central and southeast Nigeria

Abstract: Host range experiments and field sampling in Nigeria produced no evidence that African rice gall midge, Orseolia oryzivora Harris & Gagné, can develop on plants other than Oryza species. Sampling in three outbreak areas during 1994 showed that the insect's annual cycle varied according to the agroecological zone and rice cropping pattern. In the humid forest zone, Orseolia oryzivora persisted through the short dry season on ratoons of cultivated rice Oryza sativa at a rainfed site and on dry season rice crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…During these months, the mean relative humidity and temperature averaged 75% and 25 8C, respectively, and this has been reported as favourable for AfRGM development and reproduction (Umeh and Joshi, 1993). Previous studies have established a link between the weather, especially rainfall during the wet season, and AfRGM rate of infestation and development (Umeh and Joshi, 1993;Williams et al, 1999). Umeh and Joshi (1993) observed that the peaks in AfRGM populations were positively correlated with increase in relative humidity and regular rainfall.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…During these months, the mean relative humidity and temperature averaged 75% and 25 8C, respectively, and this has been reported as favourable for AfRGM development and reproduction (Umeh and Joshi, 1993). Previous studies have established a link between the weather, especially rainfall during the wet season, and AfRGM rate of infestation and development (Umeh and Joshi, 1993;Williams et al, 1999). Umeh and Joshi (1993) observed that the peaks in AfRGM populations were positively correlated with increase in relative humidity and regular rainfall.…”
Section: Discussionmentioning
confidence: 81%
“…The African rice gall midge (AfRGM) Orseolia oryzivora Harris and Gagné (Diptera: Cecidomyiidae) is an important insect pest of rainfed and irrigated lowland rice in Africa (Williams et al, 1999;Nwilene et al, 2006). It has also been reported in the rainfed upland ecology in Burkina Faso (Dakouo et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wild rice appears to play an important role in the survival of stemborers and diopsid flies between the rice-cropping seasons. (Williams et al, 1999). However, O. longistaminata is not the only alternate host plant of lepidopteran stemborers and diopsid flies.…”
Section: Discussionmentioning
confidence: 99%